Impact of high-dose anti-infective agents on the osteogenic response of mesenchymal stem cells - Hofmann, Jakob; Klingele, Sabrina; Haberkorn, Uwe; Schmidmaier, Gerhard; Großner, Tobias (Antibiotics, 2021)
Treatment of infected nonunions and severe bone infections is a huge challenge in modern orthopedics. Their treatment routinely includes the use of anti-infective agents. Although frequently used, little is known about their impact on the osteogenesis of mesenchymal stem cells. In a high- and low-dose set-up, this study evaluates the effects of the antibiotics Gentamicin and Vancomycin as well as the antifungal agent Voriconazole on the ability of mesenchymal stem cells to differentiate into osteoblast-like cells and synthesize hydroxyapatite in a monolayer cell culture. The osteogenic activity was assessed by measuring calcium and phosphate concentrations as well as alkaline phosphatase activity and osteocalcin concentration in the cell culture medium supernatant. The amount of hydroxyapatite was measured directly by radioactive 99mTechnetium-HDP labeling. Regarding the osteogenic markers, it could be concluded that the osteogenesis was successful within the groups treated with osteogenic cell culture media. The results revealed that all anti-infective agents have a cytotoxic effect on mesenchymal stem cells, especially in higher concentrations, whereas the measured absolute amount of hydroxyapatite was independent of the anti-infective agent used. Normed to the number of cells it can therefore be concluded that the above-mentioned anti-infective agents actually have a positive effect on osteogenesis while high-dose Gentamycin, in particular, is apparently capable of boosting the deposition of minerals.
Gesehen am 04.01.2022